A new species of the thorid shrimp genus Lebbeus White, 1847 (Decapoda: Caridea) from the Amami Rift hydrothermal vent field in the Ryukyu region, Japan - Komai, Tomoyuki; Chen, Chong (Zootaxa, 2024)
A new species of the thorid shrimp genus Lebbeus White, 1847, is described and illustrated on the basis of two specimens collected from the recently discovered Amami Rift hot vent field in the Ryukyu region in southwestern Japan, at a depth of 628 m. Lebbeus parvirostris sp. nov. is morphologically similar to L. microceros (Krøyer, 1841), L. mundus Jensen, 2006, L. saldanhae (Barnard, 1947), L. schrencki (Bražnikov, 1907), L. spongiaris Komai, 2001, and L. tosaensis Hanamura & Abe, 2003, but differs from all of them in the lack of a pterygostomial tooth on the carapace in the female. Other diagnostic characters useful in differentiating the new species from the aforementioned close relatives are also discussed. Genetic analyses using sequences of two mitochondrial markers, including cytochrome c oxidase subunit I (COI) and 16S rRNA, are also presented to provide preliminary support for the status of the new species. Lebbeus parvirostris sp. nov. is the second representative of Lebbeus known from active hydrothermal vents in the Ryukyu region.